NUTRITION AND EARLY DEVELOPMENT: A FRAMEWORK FOR THRIVING CHILDREN - Rahmon Aslanovich, Amanov (PT. Antis International Publisher, 2024)
Objective: To explore the importance of integrating nutrition and responsive caregiving in promoting child development, particularly in low- and middle-income countries (LMICs), where children face higher risks of malnutrition and developmental vulnerabilities. Methods: The study employed a targeted literature review and qualitative synthesis of key frameworks, including the Nurturing Care Framework and the Conceptual Framework for All Children Surviving and Thriving. It analyzed intervention outcomes focusing on physical, cognitive, and emotional developmental domains. Results: Findings reveal that integrated interventions combining nutrition and responsive caregiving lead to significantly better child development outcomes compared to nutrition-only programs. Children receiving integrated care showed improvements in physical growth, cognitive abilities, socioemotional well-being, and overall development. This underscores the importance of adopting holistic, multisectoral approaches that prioritize nurturing care and early learning alongside physical health. Novelty: This study highlights the critical gap in previous research, which often overlooked the role of nurturing care in cognitive and socioemotional growth. It emphasizes the need for comprehensive, context-specific strategies to scale up integrated child development interventions in LMICs, aiming to address resource constraints and enhance global child health policies.